ChemInform Abstract: Rhodium(II)‐Catalyzed Tandem Aziridination and Ring‐Opening: Stereoselective Synthesis of Functionalized Tetrahydrofurans. Issue 8 (February 2015) - Unsworth, William P.; Clark, Nicola; Ronson, Thomas O.; Stevens, Kiri; Thompson, Amber L.; Lamont, Scott G.; Robertson, Jeremy
Abstract Compounds (IV) and (V) are isolated as a mixture.